A critical attitude and its influence on behavior change in terms of forming a negative position towards governmental mitigation measures during a pandemic - O. H. Kempkens (Вестник университета)
As a strategy against the outbreak and the further spreading of Covid-19, countries, states and communities used different approaches. To protect citizens, governments developed coronavirus mitigation measures and due to which, people were confronted with restrictions in their everyday life. As could be observed in many countries, the society mood turned, since many people did not agree with these restrictions and some people even started demonstrating against governmental mitigation measures. In this context, it can be assumed that some people are more prone to believe in rumors and fake news spread on social media than others. Consequently, a critical attitude is being developed against the government and/or Covid-19 mitigation measures. The present study uses the quantitative data collection method to investigate why some people change their behavior in crises situations and why they are more prone to believing rumors and fake news on social media than others. The results showed that the higher people rate themselves as being critical, the less they believe in rumors and fake news on social media, the less they change their behavior during the pandemic in terms of rejecting Covid-19 mitigation measures. Therefore, it is also more likely that people will follow the measures to mitigate the effects of coronavirus infection.